2001
DOI: 10.1080/0300443011670107
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of Parents’ Experiences in Parent Education Groups

Abstract: While parent education is recognized as a useful construct, practitioners often have little picture of the critical elements necessary for parent education to succeed. The study reported utilized qualitative methods to attain deeper insight into the dynamics underlying the reported benefits and outcomes of parent education in order to inform practice. Fifteen mothers at three sites across the Midwest were interviewed after participating in a parent education program based on the theory of Re-evaluation Counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…She had previously thought that she had a lot of problems with parenting but found that others shared the same problems, which made her feel supported. This is consistent with previous findings on the effectiveness of parenting programmes, which have shown that parents tend to feel supported within the programme (Barlow et al., 2004; Moran, Ghate, & Van Der Merwe, 2004; Wolfe & Haddy, 2001).…”
Section: Study Findingssupporting
confidence: 93%
“…She had previously thought that she had a lot of problems with parenting but found that others shared the same problems, which made her feel supported. This is consistent with previous findings on the effectiveness of parenting programmes, which have shown that parents tend to feel supported within the programme (Barlow et al., 2004; Moran, Ghate, & Van Der Merwe, 2004; Wolfe & Haddy, 2001).…”
Section: Study Findingssupporting
confidence: 93%
“…The transition to parenthood can be particularly challenging for individuals with a history of maltreatment and the complexity of attempting to break intergenerational cycles is highlighted (Christie et al 2017;Madden et al 2015). The value of supporting parents in the often difficult process of reflecting on their own experience of being parented is emphasised; the potential benefits of creating the opportunity for this within the delivery of parenting programmes should be considered (Levac et al 2008;Wolfe and Haddy 2001).…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Moreover, based on the findings of a phenomenological study, First and Way [28] further suggested that parenting wisdom will be amassed through transformative learning. The qualitative study conducted by Wolfe and Haddy [29] also found that parent education programs with emphasis on and recognition of parents' life experiences and generation of meaningful interactions with children can enhance parents' awareness, sense of empowerment, social support, and parenting competency. Furthermore, an outcome evaluation study of the Nobody's Perfect Parenting Programme, which emphasized the experiential knowledge generated by parents and the promotion of active group participation, indicated a significantly increased level of parenting resourcefulness, better parent-child interactions, and more effective child management [30].…”
Section: The Significance Of Addressing Parents' Existential Concernsmentioning
confidence: 99%
“…What they need is not only to acknowledge and reflect on what has happened to them, but also to find some persons to listen to, understand, and support them. Parent education in groups has been an effective method for providing mutual aid among parents [29,40]. The support from other parents can allow them to instil hope and encourage them not to give up while feeling powerless.…”
Section: Cultivation Of Mutual Support and Mutual Learning Through Pomentioning
confidence: 99%